KERAGAMAN FUNGI MIKORIZA ARBUSKULAR (FMA) DARI BEBERAPA VEGETASI LAHAN GAMBUT - Nizari Muhtarom; Iwan Sasli; Fadjar Rianto (Perkebunan dan Lahan Tropika, 2019)
The West Kalimantan land is mostly dominated by marginal peat land types. The West Kalimantan peat swamp land has a very low pH, low nutrient availability, low base saturation, high nutrient washing rates, and even some of them are sandy soil which is in the lower layers. One way to utilize peat marginal land as an agricultural crop is by utilizing Arbuscular Mycorrhizal Fungi (FMA) as biological fertilizer inoculums. The stages of the research are the exploration of FMA from several root zone plants from two locations, Galang and Rasau Jaya Villages, then identification of FMA in the plant disease laboratory of Tanjungpura University's Faculty of Agriculture. The study was carried out for ± 3 months. The design used is by using purposive sampling method, with the number of sample points on three commodities, namely pineapple, fern and grass, each of 9 sample points. The results showed an analysis of the content of the number of FMA spores found in the highest root rooting zone found in the source of pineapple inoculums, with the number of FMA spores found as many as 96, with soil samples each of 50 g samples. Whereas the fern media amounted to 55, and the grass media amounted to 22. The highest level of FMA diversity was found in the treatment with the source of pineapple inoculum from Galang, with the discovery of three types of FMA namely genus Glomus sp, Gigaspora sp and Acaulospora sp. Keywords: arbuscular mycorrhizal fungi (AMF), exploration, marginal peat soi